DINAMIKA PERBERASAN DI SULAWESI TENGGARA - ABIDIN, ZAINAL; -, IDRIS; SYAM, AMIRUDDIN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
The research aimed to know dynamics of rice related to rice system in South East Sulawesi was done in September to Oktober 2004 in Kendari regency (Uepai, Amonggedo, Pondidaha and Abuki district). This research used survey methode involved 40 responden. The data used secundary data having the caracter of time series and primary data. The resulth showed that wet paddy production was very fluctuantive. Their productivity was related stable at 3,5 – 3,8 t/ha. Dry land paddy was wide enough used by farmer especialy in area that had poor paddy field, but wide area and its production had overtime trend while production increased. That productivity was still lower than national productivity of 2,52 t/ha. Although main production more increase in the latest of 10 years, but the government represented by Bulog still brought rice from out side South East Sulawesi especially from South Sulawesi. Rice farming system was showed R/C > 1 value. Than, exchange value of benefict on cost, the use of cost was still dominated by labour. The benefict used for labour was 29 %. Rice farming system contributed around 75 % of total househould income, besides that, farmer also obtained income from the other farming system, livestock and off-farm.
Keywords: Dinamics, Rice, South East Sulawesi